The librettist of Venice : the remarkable life of Lorenzo Da Ponte, Mozart's poet, Casanova's friend, and Italian opera's impresario in America /: the remarkable life of Lorenzo Da Ponte, Mozart's poet, Casanova's friend, and Italian opera's impresario in America. (2006) - Unknown
No abstract available